Development of Blind Massage Services in Wara Timur District, Palopo City, South Sulawesi Province - Firmansyah Dahlan (Jurnal Berkarya Pengabdian Masyarakat, 2019)
The Community Partnership Program "Development of the Blind Massage Services in East Wara Subdistrict, Palopo City, South Sulawesi Province" is aimed at: (1) Developing and enhancing the participation of people with disabilities in the national and regional development, (2) Improving the standard of living of the Blind , as an effort aimed at absorbing workforce among disabiltas in Palopo City. Massage comes from the Arabic word "mash" which means "to press gently" or the Greek word "massien" which means "to massage or to scrub". Furthermore, massage is also referred to as the science of massage or lulut science. The focus of massage developed in the Community Blind Massage Program "Blind Massage Services in Palopo City, South Sulawesi Province, namely Massage Health, Therapy and Sports (recovery and sports injuries). Disabilities tendency of the Blind have disabilities and expertise to perform massage services because the Blind in the disabilities in every activity he does on a daily basis rely on the sense of "touch" especially the palm of the hand so that it has more sensitivity than humans in general. This is what makes the blind people with disabilities have talents and expertise in the field of massage or sciences. Partners in the Community Partnership Program are the Harapan Sehat Massage Clinic. Mitra has run a business and Massage Service with a turnover of Rp. 3,000,000 to Rp. 4,000,000 per month, while the number of workers joined in this business unit is five (4) people. Partner problems include service quality (production results), business management, marketing systems. Partner Issues Include: (1) The quality of services that are still traditional so that they lack attractiveness and trust in the wider community, so it is necessary to develop a massage / massage capability that leads to a standard and scientific health approach; (2) Participating in training or providing training for the Blind Massage Services; (3) Touch of massage technology; (4) Business management, there is no business management pattern that meets the standards and the division of work has not been directed and business motivation is lacking due to disability factors; (5) The marketing system, information patterns and publications are still very traditional, that is, from the mouth-mouth so that it becomes a separate obstacle in seizing potential markets; (6) Does not have a clear business plan; (7) Lack of capital to establish a Blind Massage Services clinic and attend massage training in order to have an increase in the ability of more scientific and scientific massage services. Based on the complexity of these problems, this dedication activity will focus on the development of Business Management and Development of massage (massage) service capabilities. The program is carried out in 3 (three) stages, namely: the flow of the PKM program starts from, 1) the preparation phase, 2) the implementation phase, and 3) the monitoring and evaluation phase. Key Word: Blind, Massage Services.